THE EFFECT OF FACILITIES ON THE STUDENTS' LEARNING MOTIVATION OF THE ARCHITECTURE STUDY OF UPN "VETERANS" EAST JAVA - Marnisari, Jelita Arrum (Border: Jurnal Arsitektur, 2021)
The realization of academic achievement in higher education is very dependent on the motivation to learn on the students themselves. However, there are many factors that can affect the presence of learning motivation, both external and internal factors. Several external factors exist, including the quality of infrastructure that supports the teaching and learning process of students. Several infrastructure facilities (sarpras) in the Architecture Study Program building, East Java "Veteran" National Development University (UPNVJT) have been used for decades, since the establishment of the Architecture Study Program. It is feared that the old Sarpras can affect students' learning motivation, especially if the existing Sarpras are not relevant to current learning needs. However, there have been several new sarpras that have been presented in the Architecture Study Program to support the student learning process. Therefore, this study aims to determine how much influence the available facilities and infrastructure have on learning motivation and academic achievement of UPNVJT Architecture Study Program students. This research was carried out by examining several available infrastructures in the Architecture Study Program of UPNVJT. Student learning motivation variable data obtained through a questionnaire that will be associated with the conditions of the available facilities. The results of the study found that the means had an indirect relationship and was not the main factor that determined students' learning motivation.